Correction: Assessing the exchange coupling in binuclear lanthanide(iii) complexes and the slow relaxation of the magnetization in the antiferromagnetically coupled Dy2 derivative. Issue 8 (14th August 2015) - Chow, Chun Y.; Bolvin, Hélène; Campbell, Victoria E.; Guillot, Régis; Kampf, Jeff W.; Wernsdorfer, Wolfgang; Gendron, Frédéric; Autschbach, Jochen; Pecoraro, Vincent L.; Mallah, Talal
<x xml:space="preserve">Abstract</x> Correction for 'Assessing the exchange coupling in binuclear lanthanide(iii) complexes and the slow relaxation of the magnetization in the antiferromagnetically coupled Dy2 derivative' by Chun Y. Chow et al., Chem. Sci., 2015, 6, 4148–4159.